Family Connect: Keeping families informed during the COVID-19 pandemic - Brittany Branson (The Beryl Institute, 2020)
Family Connect programs to enhance communication with families and care partners who were unable to visit their inpatient loved ones during the COVID-19 crisis. While they differed in composition, the Family Connect programs at both institutions leveraged providers who had decreased clinical activity during the pandemic. The Family Connect team became integrated with the team. At both institutions, Family Connect teams perform virtual chart review, discuss patient status and care plan with the primary provider and communicate with the patient’s designated family member or care partner daily. Conversations are documented in the electronic medical record (EMR), which allows for metric tracking and clear communication to all team members. All Family Connect providers undergo a comprehensive training program focused on workflow, communication, and EMR training. Family Connect can be tailored to the needs of specific health systems based on patient volume and staffing. The NYULH Family Connect model incorporated medical student mentorship, on-site nurse liaisons to assist patients with virtual visits with families, and a 24/7 call center for family support. The YNHHS model was separate from the YNHHS COVID-19 call center and utilized attending and trainee physicians. The program is highly portable and can be easily reinitiated if needed. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.